Occurrence of Interspecific Mating between Two Species of Danaus Kluk, 1780 (Lepidoptera: Nymphalidae) in Nature - Sarika Baidya; Dipendra Nath Basu; Souparno Roy; Arjan Basu Roy (Psyche: A Journal of Entomology)
Mating across species occurs rarely in nature, which contends prevalent idea of biological species concept. Throughout species range, mating pattern varies and reproductive barriers are also not fixed among different species. In this study, two instances of interspecific mating between two widely common Nymphalid Tiger butterflies (Danaus Kluk, 1780) in Indian region are reported. Observations imply lack of absolute reproductive barriers, where possible interplay exists among prezygotic and postzygotic isolating factors compensating each other in order to restrain interspecific hybridization.